Ценностно-смысловые характеристики как предикторы созависимого поведения женщин, проживающих с наркозависимым партнером - Коленова, Анастасия; Гурцкой, Дмитрий (Rossijskij psihologičeskij žurnal., 2019)
Introduction. This paper discusses the results of a comprehensive survey that involved respondents from various regions of the South of the Russian Federation and represents the first report on psychological characteristics of codependent behavior and value-meaning sphere in young women of different ethnic groups. The novelty of the study lies in the development of psychological models of codependent behaviors for each ethnic group studied in order to further develop psycho-correction techniques of working with youth in south Russia. Methods. The sample consisted of 330 respondents with various levels of codependent behaviour residing in three federal subjects of the South of the Russian Federation. The respondents ranged in age from 17 to 30 years.  The study used the following standardized and projective techniques to reveal differences in value-meaning sphere among young women of different ethnic groups: (a) the Spann‐Fisher Codependency Scale, SFCDS (modified by Moskalenko), (b) the Purpose-in-Life Test, PIL (developed by Crumbaugh & Maholic, modified by Leont'ev), (c) the Personal Orientation Inventory, POI (developed by Shostrom, modified by Kalin), (d) the Bass Orientation Inventory, (e) the technique for studying self-assessment using the procedure for ranking (developed by Rean), (f)  the Value Orientations technique (developed by Rokich), and (g) the Write-a-Story technique (stimulus materials from Tables 2, 4, and 6, Thematic Apperception Test). The STATISTICA, a statistical package software version 10.0, was used for data processing. Results. The individual participants of different ethnic groups had significant differences in characteristics of codependence, both in terms of the dynamics of situational assessment and in the content of stable personal constructs. Discussion. Despite of similar trends in manifestations of codependence, the representatives of different ethnic groups are characterized by certain distinguishing characteristics, which manifest themselves in interpersonal communication with addicts and the environment and also in self-acceptance. Введение. В данной статье рассматриваются результаты проведенного комплексного обследования респондентов различных регионов Юга РФ, которые позволили впервые получить данные о психологических особенностях проявления созависимого поведения, а также о специфике ценностно-смысловой сферы у молодых женщин с различной этнической принадлежностью. Новизна исследования заключается в разработке психологических моделей созависимого поведения, характерных для каждой выделенной подгруппы (этнической принадлежности) с целью дальнейшей разработки психокоррекционных мероприятий для молодежи, проживающей на Юге РФ. Методы. В исследовании было обследовано 330 женщин, проживающих в трех субъектах Юга РФ в возрасте от 17 до 30 лет, проявляющих различную степень созависимого поведения. Были использованы стандартизированные и проективные методики, которые предоставили возможность выявить различия в ценностно-смысловой сфере у молодых женщин с различной этнической принадлежностью, проявляющих созависимое поведение: «Шкала измерения созависимости в отношениях Спанн – Фишер» (адаптация Москаленко), «Тест смысложизненных ориентаций» («PIL» Крамбо и Махолик в модификации Леонтьева), «Методика самоактуализации POI Шострома» (модификация Калина), опросник направленности личности (ориентационная анкета) Басса, «Методика изучения самооценки с помощью процедуры ранжирования» Реана, методика «Ценностные ориентации» Рокича, методика «Напиши рассказ» (стимульный материал таблиц № 2, 4, 6 «Тематического апперцептивного теста»). Статистические методы обработки данных осуществлялась при помощи пакета компьютерных программ «STATISTICA 10.0». Результаты. В результате проведенного исследования установлено, что у респондентов с различной этнической принадлежностью существуют значимые отличия в характеристике проявления созависимости, как в части динамики ситуативной оценки, так и в содержании устойчивых личностных конструктов. Обсуждение результатов. При общих схожих тенденциях в проявлении созависимости у представителей различных этнических групп можно выделить особенности, отличающие и характеризующие их, что проявляется в межличностном общении с зависимым, с окружением и в принятии себя.